Transcranial Electrical Stimulation Offers the Possibility of Improving Teamwork Among Military Pilots: A Review - Lu, Hongliang; Zhang, Yajuan; Huang, Peng; Zhang, Yan; Cheng, Sizhe; Zhu, Xia (Frontiers in Neuroscience, 2022)
Effective teamwork among military pilots is key to successful mission completion. The underlying neural mechanism of teamwork is thought to be inter-brain synchronization (IBS). IBS could also be explained as an incidental phenomenon of cooperative behavior, but the causality between IBS and cooperative behavior could be clarified by directly producing IBS through extra external stimuli applied to functional brain regions. As a non-invasive technology for altering brain function, transcranial electrical stimulation might have the potential to explore whether top-down enhancement of the synchronization of multiple brains can change cooperative behavioral performance among members of a team. This review focuses on the characteristic features of teamwork among military pilots and variations in neuroimaging obtained by hyper-scanning. Furthermore, we discuss the possibility that transcranial electrical stimulation could be used to improve teamwork among military pilots, try to provide a feasible design for doing so, and emphasize crucial aspects to be addressed by future research.